2020
DOI: 10.1002/bco2.43
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of automated bone scan index for predicting overall survival among bone metastatic castration resistant prostate cancer patients treated with radium‐223

Abstract: Introduction The objective of this study was to evaluate automated bone scan index (aBSI) as a prognostic biomarker for overall survival (OS) in bone‐metastatic, castration‐resistant prostate cancer (mCRPC) patients treated with radium‐223 (Ra‐223). Materials and methods We identified 42 men treated with Ra‐223 for mCRPC. We investigated aBSI as an independent prognostic factor by multivariate analysis. Moreover, we evaluated the prognostic value of the aBSI after 12 weeks after the first cycle of Ra‐223 admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(119 reference statements)
1
4
1
Order By: Relevance
“… 4 , 10 13 The bone scan index has also been used as a metastatic bone disease quantifier and predictor of Ra-223 biochemical responses; however, we did not collect data on the bone scan index in the present study. 14 16 PSA levels were previously shown to sometimes become elevated during the first three cycles of Ra-223 due to the flare phenomenon; however, the flare phenomenon was not detected in the present study. 17 The present results showed that Hb, leukocyte, and ALP levels were significantly reduced in patients after the planned six Ra-223 injections; however, it was considered to be difficult to evaluate them individually.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“… 4 , 10 13 The bone scan index has also been used as a metastatic bone disease quantifier and predictor of Ra-223 biochemical responses; however, we did not collect data on the bone scan index in the present study. 14 16 PSA levels were previously shown to sometimes become elevated during the first three cycles of Ra-223 due to the flare phenomenon; however, the flare phenomenon was not detected in the present study. 17 The present results showed that Hb, leukocyte, and ALP levels were significantly reduced in patients after the planned six Ra-223 injections; however, it was considered to be difficult to evaluate them individually.…”
Section: Discussioncontrasting
confidence: 83%
“…PSADT is a commonly used indicator of distant metastasis among patients treated with ADT and radiation therapy; however, it currently remains unclear whether PSADT after treatment with Ra-223 reflects therapeutic effects and the subsequent clinical course. 4 , 11 16 Based on the present study, PSADT after the Ra-223 treatment was a useful indicator for estimating the clinical course following treatment.…”
Section: Discussionmentioning
confidence: 76%
“…In the univariate analysis, associations between the median BSI and 2D-TBU values at baseline and radium-223 treatment completion were confirmed. The results of this study are consistent with those of several previous studies, which confirmed associations of these indices with radium-223 treatment [24][25][26][27]. In the survival analysis, patients who completed the radium-223 treatment regimen showed a significantly longer median OS.…”
Section: Dittmann Et Al and Oya Et Al Reported That A Quantitative As...supporting
confidence: 92%
“…Various studies have used blood markers and imaging indices for patient selection to determine who would most likely benefit from radium-223 treatment [6-8,19-PSA; high levels of Hgb were significant factors associated with treatment completion [6][7][8]. Additionally, the active bone metastatic burden spread-based BSI is commonly used imaging index to evaluate patients treated with radium-223 [24][25][26]. Kitajima et al developed a novel nomogram, including BSI, to select patients with mCRPC to receive radium-223 treatment, and this nomogram was shown to be suitable for assisting therapeutic decision-making [27].…”
Section: Discussionmentioning
confidence: 99%
“…Again, showing patterns of multiple sites (bone/viscera), and higher rates of lung metastases. To the Clinic… We have two articles for the clinic in this issue from Japan. The paper by Miyoshi et al 5 uses a tool you may or may not be using called an automated bone scan index (aBSI), a tool to objectively quantitate bone metastases burden. They used this index specifically in castrate resistant prostate cancer treated with Radium‐223.…”
Section: Figurementioning
confidence: 99%